[OP.7D.10] THE EFFECT OF RENAL DENERVATION ON ADIPOKINES IN PATIENTS WITH RESISTANT HYPERTENSION. (September 2016) - Eikelis, N.; Hering, D.; Marusic, P.; Walton, A.; Lambert, E.; Krum, H.; Lambert, G.; Esler, M.; Schlaich, M.
Abstract : Objective: We have previously demonstrated the effectiveness of renal denervation (RDN) to lower blood pressure (BP) at least partially via the reduction of sympathetic stimulation to the kidney. Obesity also contributes to hypertension. A number of adipocyte-derived factors (collectively termed 'adipokines') have been implicated in BP control. The aim of this study was to examine the effect of RDN on adipokines. In particular, whether BP reduction, associated with RDN treatment, has a favourable outcome on adipokine profile in patients with resistant hypertension (RH). Design and method: Fifty seven patients with RH undergoing RDN have been recruited for the study (65% males, age 60.8 ± 1.5 years, BMI 32.6 ± 0.7 kg/m 2, mean ± SEM). At recruitment the patients were on an average of 4.8 ± 2.1 antihypertensive drugs and were asked to refrain from changing their medication regimen for the duration of the study. Automated seated office BP measurements were taken with an Omron HEM-705 monitor at baseline and 3 months follow up visit. Leptin, insulin, non-esterified fatty acids (NEFA), adiponectin and resistin were measured in plasma at baseline and 3 months after RDN. Results: There was a significant reduction in mean office systolic (168.75 ± 2.57 vs 155.23 ± 3.17 mmHg, p < 0.001) and diastolic (90.68 ± 2.31 vs 83.74 ± 2.36 mmHg, p < 0.001) BP 3 months after RDN. Body weight and heart rate remained unchanged. There were no significant differences in plasma leptin levels post RDN. Fasting insulin concentration significantly increased 3 months after the procedure (20.05 ± 1.46 vs 29.70 ± 2.51 uU/ml, p = 0.002). There was a significant drop in circulating NEFA at follow up (1.01 ± 0.07 vs 0.47 ± 0.04 mEq/l, p < 0.001). While there were no changes in resistin, adiponectin concentration was significantly higher after RDN (5654 ± 800 vs 6644 ± 967 ng/ml, p = 0.024). Conclusions: We have previously shown a decrease in BP following RDN. This is the first study to demonstrate that RDN is associated with potentially beneficial effects on the adipokine profile. Increased adiponectin and reduced NEFA production may contribute to BP reduction via metabolic pathways.